Faculty Attitudes on Outcomes-Based Education Implementation in Lao Higher Education Institutions: A Case Study of Social Science Programs - Machang, Ayyia; Yongxia , Ma; Mingboubpha , Houmlack (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The development of a higher education curriculum integrated with the regional and international curriculum development framework to facilitate student mobility, credit transfer, and the requirements of the local labor market for academics with knowledge, ability, and skills in their specific field had become a necessary issue to transform from traditional education to outcomes-based education at the higher education in Laos. Thus, the objective of this study is to investigate the attitude of faculty toward OBE implementation at higher education institutions in Laos. The authors employed a quantitative approach to collect data, and the questionnaire was responded by 283 faculty members. The findings showed that 73% of the instructor strongly agree and agree with the OBE approach and results revealed that faculty members’ attitude toward OBE approach with the mean score of 3.90 to the test value of 4, it also found that instructors’ acceptance of OBE is the highest (Ac = 4.05) and their knowledge is the lowest (Kn= 3.63). The teaching experiences and OBE training were significant impact on faculty members’ attitude toward OBE implementation. However, the findings of this study also revealed that a number of instructors still have a less-than-ideal attitude toward OBE implementation.